Filosofi Makna Bentuk Ornamen - Yeni, Novita Indra; Dafrina, Armelia; Muliana, Erna (Universitas Syiah Kuala, 2025)
The research examines the philosophy, meaning, form, and ornament of the Pagaruyung City Basa Palace as a representation of Minangkabau cultural values. The Minangkabau people are used to learning a lot from nature that has become their life's grip. Through various decorative motifs, the Minang people try to introduce their way of thinking which is inspired by nature. As a cultural heritage or heirloom of a culture and beauty, the Basa Palace of Pagaruyung City holds many advice or life lessons contained in the symbols present on the ornaments. A philosophy that underlies the life of the Minangkabau people, namely